An integrated strategy to discover Lactobacillus casei group strains for their potential use as aromatic starters. (October 2017) - Bancalari, Elena; Savo Sardaro, Maria Luisa; Levante, Alessia; Marseglia, Angela; Caligiani, Augusta; Lazzi, Camilla; Neviani, Erasmo; Gatti, Monica
Abstract: Lactic acid bacteria are commonly used in dairy industries to acidify milk and to enhance the flavour of the end products thanks to their metabolisms. The formation routes of aroma compounds mainly rely on the specific ability of different species and strains to convert precursors derived from carbohydrate and amino acids catabolism. It is well known that the strains largely involved in the aroma formation of the very appreciated Italian long ripened cheeses belong to the Lactobacillus casei group and origin from raw milk. In this study, a spontaneous fermentation of Parmigiano Reggiano raw milks was carried out to isolate new strains potentially usable as adjunctive aromatic starter. For this reason, specific selection criteria were chosen to isolate strains belonging to L. casei, and L. paracasei species. An integrated approach, by mean of impedance microbiology and SPME GC–MS analysis, was applied to investigate the acidifying performance and the production of volatile compounds of seven strains in UHT whole milk. One of these strains, L. paracasei 4341, appear to be the most interesting one from the technological point of view both for its acidifying and aromatic features. This approach could be employed for selection of the aromatic strains to be potentially used as adjunct starter in dairy sector. Graphical abstract: Highlights: Strategy to research new strains to use as adjunctive aromatic starter is proposed. Spontaneous fermentation of raw milks for four months at 8 °C Specific criteria to reduce the number of the isolates and select the best strain Integrated approach by mean of impedance microbiology and SPME GC–MS analysis